2000
DOI: 10.1076/0929-7049(200003)6:1;1-b;ft037
|View full text |Cite
|
Sign up to set email alerts
|

Executive Functions in Dyslexia

Abstract: This study focused on executive functions in dyslexia. A group of 43 heavily-affected young dyslexics, divided into two groups based on the results of a receptive language test, and 20 non-dyslexic controls, were tested with a Dichotic Listening Test, the Stroop Color Word Test and the Wisconsin Card Sorting Test. The dyslexic subjects demonstrated significant impairment on all tasks, but with different patterns of impairment according to the subgrouping. The subgroups were equally impaired on the Dichotic Lis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

14
103
5
3

Year Published

2004
2004
2018
2018

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 146 publications
(130 citation statements)
references
References 9 publications
14
103
5
3
Order By: Relevance
“…Since language impairment is associated with impaired rapid naming speed (Hulme & Mackenzie, 1992), the Stroop Colour Naming Test (Hugdahl, undated;Stroop, 1935) was used for subgroup validation. This showed a significant difference (p < .01) between subjects scoring above and below cutoff point on the Receptive Language Test, with lowest scores in the language impaired subgroup (see also Helland & Asbjørnsen, 2000.…”
Section: Variables Used For Subgroupingmentioning
confidence: 87%
See 1 more Smart Citation
“…Since language impairment is associated with impaired rapid naming speed (Hulme & Mackenzie, 1992), the Stroop Colour Naming Test (Hugdahl, undated;Stroop, 1935) was used for subgroup validation. This showed a significant difference (p < .01) between subjects scoring above and below cutoff point on the Receptive Language Test, with lowest scores in the language impaired subgroup (see also Helland & Asbjørnsen, 2000.…”
Section: Variables Used For Subgroupingmentioning
confidence: 87%
“…Also, functional language depends on good planning strategies or executive functions, which are closely linked to working memory (Luria, 1973). Helland and Asbjørnsen (2000) found that language comprehension skills in dyslexic subjects could explain variance in the performance of executive tasks. This line of arguments underlines the importance of including language development and functions in dyslexia assessment.…”
mentioning
confidence: 98%
“…Children with reading deficits often display shifting ability similar to that of control children, once differences in various covariates (e.g., IQ, general naming speed, or ADHD symptoms) are taken into account (e.g., Klorman et al, 1999;van der Sluis et al, 2004;Weyandt, Rice, Linterman, Mitzlaff, & Emert, 1998;Willcutt et al, 2001). Likewise, the inhibitory performance of children with reading and/or arithmetic related deficits is often found to be similar to that of control children, once initial differences in covariates (e.g., IQ, general naming speed or numerical skills) are controlled for (e.g., Bull & Scerif, 2001;Everatt et al 1997;Helland & Asbjørnsen, 2000;Sikora et al, 2002;van der Schoot, Licht, Horsley, & Sergeant, 2000;van der Schoot, Licht, Horsley, & Sergeant, 2002;van der Sluis et al, 2004;Willcutt et al, 2001).…”
Section: Efs and Their Relations With Reasoning Reading And Arithmeticmentioning
confidence: 97%
“…The directed attention (Bryden, Munhall, & Allard, 1983;Obrzut, Hynd, Obrzut, & Pirozzolo, 1981) or forced attention procedure (Hugdahl & Andersson, 1986) have, in addition to controlling for random biasing of attention, also shown to be useful for assessing auditory attention skills in several clinical samples, including learning disabled and reading impaired samples (Asbjørnsen & Bryden, 1998;Obrzut, Boliek, & Bryden, 1997), and psychiatric samples (Bruder, 1988;Bruder, Schnur, Fergeson, Mukherjee, et al, 1994;Hugdahl & Wester, 1992;Hugdahl, Wester, & Asbjørnsen, 1990;Loberg, Hugdahl, & Green, 1999;Nachshon, 1988;Thakur & Mukundan, 1988). Performance on directed attention dichotic tasks discriminates between groups of learning disabled children and both age and reading matched controls (Asbjørnsen & Bryden, 1998;Bakker & Kappers, 1988;Boliek, Obrzut, & Shaw, 1988;Helland & Asbjørnsen, 2000, 2001Hiscock & Kinsbourne, 1982;Hugdahl, Ellertsen, Waaler, & Kløve, 1989;Hynd, Obrzut, Weed, & Hynd, 1979;Kershner & Graham, 1995;Kershner & Micallef, 1991;Kershner & Micallef, 1992;Kershner & Morton, 1990;Obrzut, 1988;Obrzut, Boliek, & Bryden, 1997;Obrzut, Conrad, Bryden, & Boliek, 1988;Obrzut, Horgesheimer, & Boliek, 1999;Obrzut, Hynd, & Obrzut, 1983;Obrzut, Hynd, Obrzut, & Leitgeb, 1980). Few studies have addressed how DL performance could be related to the reading impairment per se and/or addi...…”
mentioning
confidence: 95%
“…For example, Obrzut, Hynd, and Obrzut (1983) found impaired scores on the Category Test with learning disabled children. Helland and Asbjørnsen (2000) reported impaired scores on both the Wisconsin Card Sorting Test (WCST) and on a Stroop test compared to age equivalent normal readers. The impairments were more obvious when language comprehension was impaired.…”
mentioning
confidence: 98%